Synthesis and photocatalytic activity of g-C3N4/ZnO composite microspheres under visible light exposure. Issue 3 (1st February 2022) - Zhang, Zhengyi; Sun, Yangshan; Wang, Youle; Yang, Yong; Wang, Pingping; Shi, Lifeng; Feng, Liang; Fang, Shuqing; Liu, Qi; Ma, Liyun; Peng, Shou; Wang, Tianhe
Abstract: In this paper, a novel g-C3 N4 /ZnO composite microspheres (CZCM) with enhanced photocatalytic activity under visible light exposure were successfully prepared by a self-assembly method followed by calcination in the air. A hierarchical structure in which ZnO microspheres were closely covered with g-C3 N4 nanosheets was constructed. The microstructure and photocatalytic activities of the CZCM were characterized. The photocatalytic property of CZCM was evaluated by degrading solution Methyl Orange (MO) and Tetracycline (TC). The effects of varied contents of g-C3 N4 on the photocatalytic capability of CZCM were systematically investigated and the results show that the optimized CZ-15% sample exhibit much higher photocatalytic degradation efficiency than that of bare g-C3 N4 or ZnO under identical conditions. The analysis of Photoluminescence (PL) and photocurrent (PC) independently conformed that the photo-induced electron-hole (e − -h + ) pairs in the CZCM were effectively generated and responsible for the observed photocatalysis. The enhanced adsorption of visible-light and the effective charge separation on the surface of CZCM enabled significant improvement of photocatalytic performance. According to the experimental results and relative energy band levels of the two semiconductors, a possible photocatalysis mechanism for the reaction process is proposed.